Association between NT‐proBNP changes and clinical outcomes in paediatric patients with heart failure: Insights from PANORAMA‐HF and PARADIGM‐HF - Robert Shaddy; Jianjian Gong; Tania Garito; Susan Solar‐Yohay; Sijia Zhang; Margaret F. Prescott; Damien Bonnet; Paul F. Kantor; Michael Burch; Chad Mao; Antoinette Cilliers; Charles Canter; et al. (ESC Heart Failure, 2025)
Abstract Aims The PANORAMA‐HF trial demonstrated significant N‐terminal pro‐B‐type natriuretic peptide (NT‐proBNP) reductions in paediatric patients with left ventricular systolic dysfunction with sacubitril/valsartan or enalapril treatment over 52 weeks. This post hoc analysis aims to correlate changes in NT‐proBNP levels with clinical outcomes in PANORAMA‐HF patients receiving either sacubitril/valsartan or enalapril. Additionally, NT‐proBNP reductions in the paediatric population were compared with a subset of adult heart failure with reduced ejection fraction (HFrEF) patients from the PARADIGM‐HF trial. Methods and results This post hoc analysis utilized data from Part 2 of the PANORAMA‐HF trial. Associations between baseline NT‐proBNP levels, changes post‐baseline and the risk of HF clinical events in paediatric patients on sacubitril/valsartan or enalapril were assessed. The paediatric HF population from PANORAMA‐HF was categorized into age groups (AG): AG1 (aged 6 to <18 years), AG2a (aged 2 to <6 years) and AG3a (aged 1 month to <2 years). The Cox proportional hazard model evaluated the relationship between NT‐proBNP and clinical outcomes. Analysis of 361 paediatric patients (sacubitril/valsartan, n = 179; enalapril, n = 182) demonstrated overall higher baseline NT‐proBNP levels in younger AGs. At Week 52, both treatment groups exhibited reduced NT‐proBNP levels across all AGs. Reductions were comparable between sacubitril/valsartan and enalapril, with a numerically greater reduction observed in adult patients versus children. Strong associations between NT‐proBNP levels and HF clinical outcomes were observed in paediatric populations in PANORAMA‐HF and in adult DCM patients with HFrEF in PARADIGM‐HF. Doubling of NT‐proBNP levels was associated with a ≥1.7‐fold increased risk of HF clinical events, while halving of the levels correlated with a 52% reduction in the risk of clinical events. Conclusions This is the first prospective, randomized large‐scale study to demonstrate a strong correlation between NT‐proBNP levels and risks of HF clinical events in paediatric patients with HF.